Reaction of 4-(4-Methylbenzoyl)-5-(4-methylphenyl)furan- 2,3-dione with Various Amides - OZER ILHAN, ILHAN; ERSAN, FAHRETTIN (Asian Journal of Chemistry, 2010)
The thermal decomposition of 4-acyl substituted furan-2,3-dione (1) leads to the α-oxo ketene (2) as an intermediate which undergoes nucleophilic addition reactions with amides. The open-chain α-N-acyl-oxo-amide derivatives (4a-f) which were obtained by these reactions show ketoenol tautomerism. The structures of all the products were confirmed by elemental analysis, IR, 1H and 13C NMR.